Circumstances and determination of individual outcomes in Bolivia: Family background and equality of opportunities (2003-2013) - Alejandro Herrera Jiménez; Horacio Villegas Quino (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 2016)
We analyze the effect of some circumstances, i.e. exogenously determined individual characteristics, over individual income and likewise over achieved years of education. Gathering information for Bolivia and applying the theoretical scheme of Equality of Opportunity, this paper identifies as relevant circumstances influencing outcomes: the individual characteristics (such as gender, ethnicity) and family background (household characteristics and parental education). We handle and compare two household surveys ten years in between, in order to analyze whether these circumstantial factors are still relevant in determining the analyzed outcomes. After appraising different econometric models, strengthened by a descriptive analysis, we find that the identified circumstances are a vital part of income determination, and even more significant part in education level determination in Bolivia. However, we also evidence that within ten years the conditioning of income to those selected circumstances is less significant for the country, suggesting that there could be improvements in the equality of opportunities.
Keywords: D31; D63; J62; 330; Inequality of opportunity; family background; parental education